Various Teaching Methods and Models of Virus Learning at High School and College Level: A Systematic Review - Hendro Gunadi; Suranto Suranto; Murni Ramli (Universitas Sebelas Maret, 2020)
The topic of viruses is closely related to the daily life and problems faced by students. The concept of viruses is considered difficult by students because they are abstract and contain many unfamiliar words. This research aimed to analyze various teaching methods and models of virus learning at the high school and college level and to find out the most suitable models or methods in learning virus concepts effectively. This study reviewed research articles published on online databases, such as Google Scholar, Eric, WorldCat, and ScienceDirect. Articles were selected using the PRISMA method with the keywords